PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 16 PADANG - Susanti, Gusri; Harisman, Yulyanti; Fitri, Dewi Yuliana (Pendidikan Matematika, 2014)
ABSTRACTThe research are motivated by lack of cooperation among student and student comprehension of matematical concept that still low.The purpose of this research is to determine wether students comprehension of mathematical concept by using cooperatif learning type Think Pair Share is better than students comprehension of mathematical concept by using conventional learning in class VIII of SMPN 16 Padang. This was an experimental research with random to subject design. The population of this research is students class VIII of SMPN 16 Padang, except class VIII 1 because itâs a superior class. The sample of this research are classÂ  VIII.3 as experiment class and class VIII.4 as control class, the instrument used is test comprehension of mathematical concept in the form of essays with r11 = 0,88. Based on the result of data anayisis, it was revealed that mean of value experiment class is higher than mean value of control class. Hypotesis test used MANN- WHITNEY, because the sample data has not normally distributed. From the calculation, it was obtained that Z = -2,056 have possibility under H0 of P = 0,1970, because it was smaller than Â = 0,05, then H0 was rejected and HI was received. Based on the hypotesis test, it can be conclude that studentsâ comprehension of mathematical concept by using cooperatif learning type Think Pair Share is better than studentsâ comprehension of mathematical concept by using conventional learning.